Integrasi Teori Psikoanalisis, Behaviorisme, dan Humanistik dalam Perencanaan Pembelajaran Pendidikan Agama Kristen - Zebua, Frendi Sofyan (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2025)
This study aims to analyze the integration of psychoanalytic, behaviorist, and humanistic theories in Christian Religious Education learning planning as a holistic and transformative approach. The main theoretical basis refers to Sigmund Freud (psychoanalysis), B.F. Skinner (behaviorism), and Abraham Maslow and Carl R. Rogers (humanistic), which are adapted in the context of Christian religious education. This study uses a descriptive qualitative method with a library study approach, which examines the literature on educational psychology, theology, and Christian religious education learning practices from various current scientific sources. The results show that psychoanalytic theory helps teachers understand students' inner dynamics and emotional conflicts, behaviorist theory emphasizes the formation of spiritual habits through positive reinforcement, while humanistic theory positions students as unique individuals who are active in the growth of faith. The integration of the three produces a Christian religious education learning model that touches on the cognitive, affective, and spiritual dimensions as a whole. Practical implications for Christian religious education teachers are the importance of developing reflective learning, consistent in the habituation of Christian values, and creating an empathetic and participatory learning space so that students experience real faith transformation. AbstrakPenelitian ini bertujuan untuk menganalisis integrasi teori psikoanalisis, behaviorisme, dan humanistik dalam perencanaan pembelajaran Pendidikan Agama Kristen sebagai pendekatan yang holistik dan transformatif. Landasan teori utama merujuk pada Sigmund Freud (psikoanalisis), B.F. Skinner (behaviorisme), serta Abraham Maslow dan Carl R. Rogers (humanistik), yang diadaptasi dalam konteks pendidikan iman Kristen. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kepustakaan, yang menelaah literatur psikologi pendidikan, teologi, dan praktik pembelajaran Pendidikan agama kristen dari berbagai sumber ilmiah terkini. Hasil penelitian menunjukkan bahwa teori psikoanalisis membantu guru memahami dinamika batin dan konflik emosional siswa, teori behaviorisme menekankan pembentukan kebiasaan rohani melalui penguatan positif, sedangkan teori humanistik menempatkan siswa sebagai pribadi unik yang aktif dalam pertumbuhan iman. Integrasi ketiganya menghasilkan model pembelajaran pendidikan agama kristen yang menyentuh dimensi kognitif, afektif, dan spiritual secara utuh. Implikasi praktis bagi guru pendidikan agama kristen adalah pentingnya mengembangkan pembelajaran yang reflektif, konsisten dalam pembiasaan nilai-nilai Kristen, serta menciptakan ruang belajar yang empatik dan partisipatif agar siswa mengalami transformasi iman yang nyata.